Kidney Cysts in Children With Alport Syndrome: A Report of 3 Cases - Yeun-Wen Chang; Daw-Yang Hwang; Tung-Ying Chen; Chun-Chen Lin; Min-Hua Tseng; Jeng-Daw Tsai (Kidney Medicine, 2024)
Alport syndrome (AS) is a progressive hereditary kidney disease characterized by hematuria, proteinuria, and progressive kidney dysfunction accompanied by sensorineural hearing loss and ocular abnormalities. Pathogenic COL4A3-5 variants can result in different AS spectra. Further, kidney cysts have been reported in adults with AS. However, the relationship between kidney cysts and AS remains unclear. Here, we report 3 cases of AS in children that occurred with kidney cysts. The patient in case 1 was initially diagnosed with IgA nephropathy at the age of 8 years but later developed bilateral multiple kidney cysts at the age of 17 years, suggesting autosomal-dominant polycystic kidney disease. Whole-exome sequencing identified a pathogenic COL4A5 variant and confirmed the AS diagnosis. The patients in cases 2 and 3 had already been diagnosed with X-linked AS using kidney biopsy and genetic analysis. Initial kidney ultrasonography showed nephromegaly; however, kidney cyst formation was observed during their annual follow-up. Our study supports the association between AS and kidney cysts. Kidney cysts in adolescents with suspected AS should not discourage clinicians from testing for pathogenic COL4A3-COL4A5 variants. Early detection of kidney cysts is critical because it may indicate kidney disease progression.